Efficiency of lung ventilation for people performing wind instruments - Anna Brzęk; Anna Famuła; Anna Kowalczyk; Ryszard Plinta (Nofer Institute of Occupational Medicine, 2016)
Background: Wind instruments musicians are particularly prone to excessive respiratory efforts. Prolonged wind instruments performing may lead to changes in respiratory tracts and thus to respiratory muscles overload. It may result in decreasing lung tissue pliability and, as a consequence, in emphysema. Aim of the research has been to describe basic spirometric parameters for wind players and causes of potential changes. Material and Methods: Slow and forced spirometry with the use of Micro Lab Viasys (Micro Medical, Great Britain) was conducted on 31 wind musicians (group A). A survey concerning playing time and frequency, weight of instruments, and education on diaphragmatic breathing was conducted. The control group included 34 healthy persons at similar age (group B). The results were statistically described using Excel and Statistica programmes. Results: The respiratory parameters were within the range of physiological norms and forced expiratory volume in 1 s to forced vital capacity (FEV1/FVC) exceeded in both groups the values of 100%. Forced vital capacity and expiratory vital capacity (EVC) values were significantly lower in the group of musicians than in the control group (p < 0.001). In 45% the group A used diaphragmatic breathing, in 31% of examinees mixed respiratory tract was observed. The significant discrepancy of individual parameters was obtained regarding age and the length of time when performing wind instrument. Conclusions: Spirometric parameters relative to standards may prove a good respiratory capacity. Peak expiratory flow (PEF) and FEV1 may indicate that a proper technique of respiration during performance was acquired. The length of time when performing wind instrument may influence parameters of dynamic spirometry. Med Pr 2016;67(4):427-433